2022
DOI: 10.1097/hjh.0000000000003269
|View full text |Cite
|
Sign up to set email alerts
|

One year of isometric exercise training for blood pressure management in men: a prospective randomized controlled study

Abstract: Objective: Isometric exercise training (IET) over 4-12 weeks is an effective antihypertensive intervention. However, blood pressure (BP) reductions are reversible if exercise is not maintained. No work to date has investigated the long-term effects of IET on resting BP.Methods: We randomized 24 unmedicated patients with high-normal BP to a 1-year wall squat IET intervention or nonintervention control group. Resting BP and various clinically important haemodynamic variables, including heart rate (HR), stroke vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
1
9
2
Order By: Relevance
“…However, the outcomes of this analysis support our previous work,24 which concluded that IET was the superior antihypertensive exercise mode. While IET may still require larger-scale longitudinal RCTs,51 55 its clinical implementation as the primary recommended exercise mode in managing blood pressure in normotensive, prehypertensive and hypertensive individuals is supported by the present results. Importantly, the previous work of Cornelissen and Smart21 included only four IET trials in 2013.…”
Section: Discussionsupporting
confidence: 64%
“…However, the outcomes of this analysis support our previous work,24 which concluded that IET was the superior antihypertensive exercise mode. While IET may still require larger-scale longitudinal RCTs,51 55 its clinical implementation as the primary recommended exercise mode in managing blood pressure in normotensive, prehypertensive and hypertensive individuals is supported by the present results. Importantly, the previous work of Cornelissen and Smart21 included only four IET trials in 2013.…”
Section: Discussionsupporting
confidence: 64%
“…Thi could attribute to reduced trainability of the heart muscle with advancing age. A recent small RCT among approximately 45-year-old men with high normal BP found that a 1-year isometric exercise training intervention reduced RHR without significant changes in cardiac output (O'Driscoll et al, 2022). In our study there was no change in RHR with higher activity levels in 30-to 65-year-old males with or without MetS.…”
Section: Discussioncontrasting
confidence: 63%
“…The study demonstrated significant office sBP reductions of -11.2 mmHg for hand grip and -12.9 mmHg for wall squat groups compared to control (-4 mmHg) but reported a larger magnitude of difference between the wall squat and control. Furthermore, the only study to investigate longitudinal efficacy of IE training as an antihypertensive intervention beyond this duration showed significant reductions (P<0.001) in clinic sBP (-9 mmHg) and dBP (-7 mmHg) compared with control following 1-year of isometric wall squat training in prehypertensive males 37 .…”
Section: Discussionmentioning
confidence: 98%